Pendampingan Penyusunan Laporan Laba Rugi Berdasarkan SAK EMKM & Koperasi Pada Usaha Mie Ayam & Bakso Solo Legowo - Susanti, Neri; Soleh, Ahmad; Sari, Nely Puspita; Sari, Meisie Novia; Panjaitan, Klara Mega Utari (Jurnal Dehasen Mengabdi, 2022)
One of the drivers of the Indonesian economy is the MSME business. This MSME business is a business that has been tested in various economic conditions. The problem is that many MSME businesses have not made financial reports. One of them is the Legowo Chicken Noodle and Meatball business which is located in Sukamerindu, Bengkulu city. Financial reports have not been considered as important reports in developing their business so that financial records are only based on sales experience, are not regular and tend to be based on estimates of the feelings of the business owner. As a result, it is difficult for business owners to determine how much the production costs of selling chicken noodles and meatballs will be and it is difficult to determine the profit or loss from the number of bowls of chicken noodles and meatballs sold. Based on these problems, this community service (PKM) aims to help legowo chicken and meatball businesses in making financial reports, especially profit and loss financial statements in accordance with SAK EMKM standards. The method used in this PKM is the method of counseling or lectures, creating discussion groups, and continuing with assistance in the practice of preparing profit and loss financial statements based on SAK EMKM from transactions that have occurred. The results of this PKM have a positive impact on the legowo chicken noodle and meatball business, where after this training, the legowo chicken noodle and meatball business owner is able to make a profit and loss financial report in accordance with SAK EMKM standards. With the making of this profit and loss financial report, the owner of the legowo chicken noodle and meatball business is able to record business books better and is able to design their business finances to be even better in the future.